Guidance and counseling in universities to support merdeka campus program - Putra, Ade Herdian; Fauziah, Febriella (Universitas Islam Negeri Raden Intan Lampung, 2022)
Humans need to improve competencies to adapt to the era of society 5.0. The inability of humans to adapt to the conditions of the times will cause problems in reducing the quality of life. To improve the quality of college graduates in society 5.0, the Minister of Education and Culture of the Republic of Indonesia made an innovation known as the Merdeka Campus program in 2020. The Merdeka Campus Program provides opportunities for active college students to study outside the program for a maximum of three semesters. Guidance and Counseling in higher education are crucial in helping students participate in the Merdeka Campus program. This study aims to describe the implementation of Guidance and Counseling in higher education to support the Merdeka Campus program. This research uses a qualitative approach with a literature study method. The data used in this study are literature reviews related to the Merdeka campus program and the implementation of Guidance and Counseling in higher education. Data analysis techniques are data reduction, data display, and verification. The results of this study indicate that Guidance and Counseling in higher education have an essential role in helping students' readiness to participate in the Merdeka Campus program. Implementing Guidance and Counseling in higher education can support the effectiveness of the Merdeka Campus program.